Self Control Peserta Didik Keluarga Broken Home di SMA Dan SMK Kecamatan Lubuk Begalung - Erfan Abdurrazaq; Mori Dianto; Rila Rahma Mulyani (JKI (Jurnal Konseling Indonesia), 2025)
The purpose of this study is to describe self-control in high school and vocational school students from broken homes in the Lubuk Begalung District. Three parts are the emphasis of this study: 1) behavior control, 2) cognitive control, and 3) decision control. The descriptive quantitative research methodology is employed. In order to collect data, self-control statements were included in questionnaires that were manually administered on paper sheets. One hundred students from phases E and F were part of the study population. Area sampling methods were used to determine the samples, which had 58 respondents in total. According to this study, kids from broken-home families in Lubuk Begalung District's high schools and vocational schools had a high degree of self-control in terms of managing their behavior, cognition, and making decisions. However, kids should continue to develop and uphold self-control, and parents and instructors should help students, particularly those from broken homes, develop strong self-control.